2000
DOI: 10.1046/j.1523-1747.2000.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Melanogenesis through Phosphatidylinositol 3-Kinase-Akt Pathway in Human G361 Melanoma Cells

Abstract: The involvement of the phosphatidylinositol 3-kinase pathway in the regulation of melanogenesis was examined using human G361 melanoma cells. In the cells treated with wortmannin, a potent inhibitor of phosphatidylinositol 3-kinase, the melanin content increased concomitant with the elevated protein level of tyrosinase, a key enzyme in melanogenesis. Northern blot analysis revealed that the mRNA level of tyrosinase increased transiently on treatment of the cells with the phosphatidylinositol 3-kinase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 50 publications
(69 reference statements)
4
100
0
Order By: Relevance
“…This phenomenon is thought to be mediated by tumor suppresser genes p16INK, retinoblastoma protein and cyclin E. 57 In other work with human melanoma cells, melanogenesis has been shown to be mediated by phosphatidylinositol 3-kinase (P13K)-Akt pathway. 58 At least in human fibroblasts the expression of MMP-1 or MMP-3 can be regulated by the mitogenactivated protein kinases (MAPKs). 59 MAPK pathways are arranged in cascades of three protein kinases, which are activated by phosphorylation in response to different stimuli, i.e., growth factors, cytokines or cellular stress.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is thought to be mediated by tumor suppresser genes p16INK, retinoblastoma protein and cyclin E. 57 In other work with human melanoma cells, melanogenesis has been shown to be mediated by phosphatidylinositol 3-kinase (P13K)-Akt pathway. 58 At least in human fibroblasts the expression of MMP-1 or MMP-3 can be regulated by the mitogenactivated protein kinases (MAPKs). 59 MAPK pathways are arranged in cascades of three protein kinases, which are activated by phosphorylation in response to different stimuli, i.e., growth factors, cytokines or cellular stress.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated CREB then binds to the CRE site on the MITF promoter, interacts with CREB binding protein (CBP) to increase the expression of MITF, and eventually causes melanogenesis (10,11). However, the ERK and Akt signaling pathways have been shown to negatively regulate melanogenesis in melanocytes (12,13). Inhibition of ERK and PI3K/Akt can cause the stimulation of melanogenesis (14,15).…”
Section: Introductionmentioning
confidence: 92%
“…The effects of wortmannin and PD98059 were also evident by FACS analyses (Figure 3b). To further confirm the action of the PI3K-AKT pathway on MelCAM expression, adenoviruses expressing active AKT (Myr-AKT) (Kohn et al, 1996) or dominant-negative PI3K (Dp85) (Oka et al, 2000) were administered to WM793 (Figure 4). Western blotting clearly showed that while activation of AKT (Myr-AKT) increased MelCAM expression, inhibition of AKT activity by a dominant-negative PI3K reduced MelCAM protein level, consistent with the pharmacological inhibition assay (Figure 3).…”
Section: Akt Activity Regulates Melcam Expression In Melanoma Cellsmentioning
confidence: 99%
“…Adenoviral vectors Myr-AKT and Dp85 were kindly provided by Dr Masahiro Oka (Sakaue et al, 1997;Kotani et al, 1999;Oka et al, 2000). Control adenoviral vector containing the LacZ cDNA (lacZ/Ad5) was purchased from Vector Core at the Institute for Human Gene Therapy of the University of Pennsylvania (Philadelphia, PA, USA).…”
Section: Adenoviral Vectorsmentioning
confidence: 99%